2010
DOI: 10.4049/jimmunol.1002803
|View full text |Cite
|
Sign up to set email alerts
|

The Inflammatory Response after an Epidermal Burn Depends on the Activities of Mouse Mast Cell Proteases 4 and 5

Abstract: Material

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
65
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 68 publications
(69 citation statements)
references
References 52 publications
4
65
0
Order By: Relevance
“…Earlier studies have shown that mMCP-4, -5, -6 and MC-CPA are strictly dependent on serglycin for their storage in secretory granules (Henningsson et al , 2002 ;Å brink et al, 2004 ;Henningsson et al , 2006 ), and here we demonstrate the absence of these proteases in serglycin −/− PCMCs ( Figure 1C). Genetic deficiency of either mMCP-4 or mMCP-6 did not substantially affect levels of other MC proteases in PCMCs, whereas MC-CPA-deficiency was accompanied by a total lack of mMCP-5, as expected due to the known interdependency of these proteases for proper storage (Feyerabend et al , 2005 ;Younan et al , 2010 ). Normal morphology and staining properties were seen in PCMCs derived from mMCP-4 −/− , mMCP-6 −/− , MC-CPA −/− and MC-CPAmut (mice with an inactivating mutation in the active site of MC-CPA) ( Figure 1A).…”
Section: Phenotype Of Cultured Peritoneal Mcsmentioning
confidence: 55%
See 1 more Smart Citation
“…Earlier studies have shown that mMCP-4, -5, -6 and MC-CPA are strictly dependent on serglycin for their storage in secretory granules (Henningsson et al , 2002 ;Å brink et al, 2004 ;Henningsson et al , 2006 ), and here we demonstrate the absence of these proteases in serglycin −/− PCMCs ( Figure 1C). Genetic deficiency of either mMCP-4 or mMCP-6 did not substantially affect levels of other MC proteases in PCMCs, whereas MC-CPA-deficiency was accompanied by a total lack of mMCP-5, as expected due to the known interdependency of these proteases for proper storage (Feyerabend et al , 2005 ;Younan et al , 2010 ). Normal morphology and staining properties were seen in PCMCs derived from mMCP-4 −/− , mMCP-6 −/− , MC-CPA −/− and MC-CPAmut (mice with an inactivating mutation in the active site of MC-CPA) ( Figure 1A).…”
Section: Phenotype Of Cultured Peritoneal Mcsmentioning
confidence: 55%
“…This, together with the known dependence of mMCP-5 on serglycin for storage (Younan et al , 2010 ), strongly implicated mMCP-5 (or other MC-CPA-dependent proteases) in the degradation of IL-13 by activated MCs. We therefore assessed the capacity of recombinant mMCP-5 to degrade IL-13.…”
Section: Recombinant Mmcp-5 Does Not Reconstitute Il-13 Degradation Bmentioning
confidence: 89%
“…Chymase has been demonstrated to induce the proliferation of cardiac fibroblasts, and to have important roles in the development of fibrosis in the lungs and heart via angiotensin II (21,22). Angiotensin II is an important growth factor in the renin-angiotensin system.…”
Section: Discussionmentioning
confidence: 99%
“…By mass spectrometry, we found Val and Ala cleavage sites in VIP or helodermin that would be predicted to be susceptible to MCPT5 (which has elastolytic activity) (48) but not to the chymase MCPT4 (47). We previously showed that the absence of MCPT4 in Mcpt4 -/-mice does not result in reduced expression or storage of other mast cell proteases (including MCPT5) (41,49,50). However, to investigate the potential role of MCPT5 in degrading VIP or helodermin, we tested the ability of PMCs from Cpa3-deficient (Cpa3 -/-) mice, which lack both CPA3 and MCPT5 proteins (51), to degrade VIP in vitro.…”
Section: Figurementioning
confidence: 99%